(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The quality of higher education depends on highly efficient, proactive and professional personnel that lead to achieving the established goals, however, in the transformation process there is a trend of high turnover in the IESP due to the workload, which generates these processes are interrupted and the goals are not met. The research aims to identify the factors that create staff turnover in IEPS. The methodology used is quantitative with the documentary technique. The first process is to review the literature and then the generation of an instrument to measure the factors that affect the attrition of staff in the IEPS. The results obtained to mention that the member of the IEPS feels that his salary does not correspond to the work done, which causes them not to feel identified with the organization and seek a salary improvement.